Hubungan Pengetahuan dan Sikap Siswa SMK Negeri 3 Kota Padang Terhadap Dampak Penggunaan Krim Pemutih Berbahaya - Dwilarani, Adinda; Dzikra, Savira Zanni; Dewi , Siska Miga (Jurnal Tata Rias, 2023)
Whitening cosmetics contain active ingredients intended to brighten or whiten the skin. Dangerous whitening cosmetics cause peeling and thinning of the skin, making it more sensitive. Most people are influenced to purchase cosmetic products, especially facial whiteners not registered with the BPOM (illegal), because these products are easily available, and they are curious about the products they will use. The popularity of these whitening cosmetics has led many students to use them to achieve better results. Based on the research problem above, the researcher aims to provide an overview, observe, gather opinions, and reveal the knowledge and attitudes of students at SMK Negeri 3 Padang City towards dangerous whitening creams. This type of research is descriptive quantitative, and the data were collected through questionnaires. The study period was March to June. The majority of respondents had poor knowledge due to a lack of information-seeking about dangerous whitening cosmetics. Students and consumers are advised to be careful when choosing facial care products, such as whitening creams, and to select products without harmful ingredients.